Ineffective Awareness of Islamic Banking Products as A Root Cause of Reluctance for the Same by Corporate Customers: A Case Study of MCB – NIB Merger in Pakistan - Zaeema Asrar Mohiuddin; Rukhshinda Begum; Farheen Zehra Rizvi (European Scientific Journal, ESJ, 2018)
This paper focuses on the lack of awareness as the major reason behind the reluctance of Corporate Customers towards Islamic Banking Products in Pakistan. Various reasons for avoiding the Islamic Banking products among customers are reflected in the literature reviewed. However, the need for further work analysis is required in the reviewed literature. Hence, the rationale for this study is to know the influence of unawareness about Islamic banking products among corporate customers and employees. This aspect was further explained through a case study. The case is based on the study of customers’ reluctance in being a part of Islamic Banking Branches. This is because M-90 branches of Ex-NIB decided to become part of MCB Islamic after merger. Nevertheless, most of the corporate customers in these branches denied to associate with MCB Islamic, but rather preferred to become a part of Corporate Conventional Banking branches of MCB Bank. Results are extracted on the basis of a detailed review of literature and reviews from the industry experts. This study will be useful to understand reasons for this unwillingness that will provide us ways to avert any shortcomings if required in the products and services being provided by the Islamic Banks.